Prizes and Lemons: Procurement of Innovation under Imperfect Commitment - Wei Ding; Elmar G. Wolfstetter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
The literature on R&D contests implicitly assumes that contestants submit their innovation regardless of its value. This ignores a potential adverse selection problem. The present paper analyzes the procurement of innovations when the procurer cannot commit to never bargain with innovators who bypass the contest. We compare ?xed-prize tournaments with and without entry fees, and optimal scoring auctions with and without minimum score requirement. Our main result is that the optimal ?xed-prize tournament is more pro?table than the optimal auction since preventing bypass is more costly in the optimal auction.
urn:nbn:de:bvb:19-epub-13290-4
Keywords: 330; innovation; contests; tournaments; auctions; bargaining; adverse; Innovationswettbewerb; Extensives Spiel; Auktionstheorie; Innovation; Beschaffung; Verhandlungstheorie; Adverse Selektion; Theorie